2011
DOI: 10.1080/00207543.2010.519000
|View full text |Cite
|
Sign up to set email alerts
|

Three decades of workload control research: a systematic review of the literature

Abstract: The workload control (WLC) concept has received much attention in the past three decades; however, a comprehensive literature review has not been presented. In response, this article provides a systematic review of the conceptual, analytical, empirical and simulation-based WLC literature. It explores the evolution of WLC research, determines the current state-of-the-art and identifies key areas for further study. The research finds that the field has evolved substantially. Early research focused on theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 110 publications
0
40
0
1
Order By: Relevance
“…Workload Control is a production planning and control concept that has been developed over more than 30 years (Thürer et al, 2011). While several different approaches to Workload Control exist, a major unifying element is the use of a load-based order release mechanism.…”
Section: Workload Control In Shops With Bottlenecksmentioning
confidence: 99%
“…Workload Control is a production planning and control concept that has been developed over more than 30 years (Thürer et al, 2011). While several different approaches to Workload Control exist, a major unifying element is the use of a load-based order release mechanism.…”
Section: Workload Control In Shops With Bottlenecksmentioning
confidence: 99%
“…Since then, many articles with a theoretical focus have followed. Simulation studies have demonstrated that WLC has the potential to improve performance (Thürer, Stevenson, and Silva 2011); however, there have been few recent successful real-world implementations Soepenberg, Land, and Gaalman 2012b). Three papers have explored practical issues associated with the WLC concept.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Section 2.1 will briefly outline the WLC concept, focusing on its original load balancing considerations. For a more extensive review of the WLC literature, in general, we refer the reader to Thürer, Stevenson, and Silva (2011). Section 2.2 then identifies complexities that are present in real-life job shops that require other considerations to enable low and controlled workloads on the shop floor.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that controlling the job input rate has a significant impact on system performance [58] [59]. This input rate can be controlled by calculating job release times that help to accomplish the target objective function, especially in the JIT context [40].…”
Section: Integration Of Job Release Timesmentioning
confidence: 99%